Risolvere senza la tecninca X SOSTITUZIONE.
Risolvere senza la tecninca X SOSTITUZIONE.
(x - 2)/(x^2 + 3·x + 2)=
=(x - 2)/((x + 1)·(x + 2))
fratti semplici:
(x - 2)/((x + 1)·(x + 2)) = Α/(x - 1) + Β/(x + 2)
(x - 2)/((x + 1)·(x + 2)) =
=(x·(Α + Β) + 2·Α - Β)/((x - 1)·(x + 2))
{Α + Β = 1
{2·Α - Β = -2
Risolvo: [Α = - 1/3 ∧ Β = 4/3]
∫((x - 2)/(x^2 + 3·x + 2)) dx= 4·LN(x + 2) - 3·LN(x + 1)
Valutato in x =1
4·LN(1 + 2) - 3·LN(1 + 1) = LN(81/8)
Valutato in x =0
4·LN(0 + 2) - 3·LN(0 + 1) = 4·LN(2)
Quindi: LN(81/8) - 4·LN(2) = LN(81/128)=
=4·LN(3) - 7·LN(2)